Fig 19 - - Dries Cnuts (2548504) (2024)
Visual characteristics of hafting residues after three-year weathering on tool exp49/44 (Rochefort; 3years): Intense fungal growth (a), dark brown discolouration of resin and beeswax (a+b), authigenic calcium deposit on resin beeswax (b), dark brown discolouration of wood hafting residues (d)) (a = x88; b = x19; c = x22; d = x120).